Akhlāq al-Muʿāmalah-Based Integrity Education for Anti-Corruption Learning in Islamic Higher Education - Arief Maulana; Mohamad Ali; Waston Waston; Wachidi Wachidi; Jobeda Khanom (SHAHIH: Journal of Islamicate Multidisciplinary, 2026)
Corruption challenges require anti-corruption education that cultivates integrity rather than merely promoting legal compliance. This study developed and evaluated an Islamic Business Ethics Education Module grounded in akhlāq al-muʿāmalah to strengthen integrity among mahasantri. Employing a Research and Development (R&D) approach guided by the ADDIE model with an embedded mixed-method design, the study comprised needs analysis, module development, expert validation, revision, implementation, and evaluation. The module was validated by nine experts and implemented with 48 students at Pondok Hajjah Nuriyah Shabran, Universitas Muhammadiyah Surakarta. Quantitative data were analyzed using Aiken’s V, descriptive statistics, and independent-samples t-tests, while qualitative data from interviews, observations, focus group discussions, and reflective journals were examined through thematic analysis. The findings indicate high content validity and significant improvements in students’ integrity awareness and ethical reasoning. More importantly, experiential learning enabled students to reinterpret fiqh al-muʿāmalah as a practical framework for accountability, transparency, and trustworthiness. The study proposes an Akhlāq al-Muʿāmalah-Based Integrity Education Model integrating Islamic jurisprudence, experiential learning, reflective moral reasoning, and critical consciousness to strengthen anti-corruption education in Islamic higher education.